The Student Achievement assisted Edmodo: An Alternative to Online Learning in the Pandemic Era - Sofia Nida Khoerunnisa; Puji Lestari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2021)
Due to the Covid-19 pandemic, face-to-face instruction in the field of education has been replaced by online learning. As a result, to meet the learning goals, teachers must be innovative and creative while delivering online learning. Student Achievement with Edmodo is one alternate online learning choice. This analysis aims to explain the effects of the introduction of Edmodo-supported Student Achievement, as well as student reactions to this learning, and to provide a single learning method that is successful and can aid teaching and learning experiences for high school mathematics content during the Covid-19 pandemic. This study employs qualitative analysis approaches. The subjects of this research were five students from Tasikmalaya City's State Senior High School. Based on the outcomes of a few experiments, it was determined that the learning experience was enjoyable and aided students' comprehension of the Trigonometry content. Students are pleased with the learning experience provided, and they believe they have made improvements as a result of their participation in the learning. According to the effects of the impact size estimation, the implementation of the Student Achievement learning model is very accurate. Then, for general student assessment, Student Achievement learning with Edmodo is beneficial to introduce in the middle of the Covid-19 pandemic, so that it can be used as a substitute in online learning.